Evaluating the Effectiveness of a Peer-Support Program in Enhancing Mental Health and Social Skills in Inclusive Elementary Classrooms in Indonesia - Choiriyah Widyasari; Siti Marpuah; Minsih Minsih; Agustina Widianti; Helzi Helzi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Inclusive education in Indonesia faces challenges related to the mental health and social skills of students with special needs. Peer-support programs are increasingly recognized as a promising approach to foster emotional well-being and social competence in inclusive classrooms. This study employed a concurrent embedded mixed-methods design, with quantitative analysis as the primary approach supported by qualitative insights. A total of 80 students with special needs (aged 8–15) from inclusive elementary schools in Surakarta were selected through purposive sampling. Quantitative data were collected using the Social Skills Improvement System (SSIS), while qualitative data were gathered through interviews, observations, and open-ended surveys. A paired-sample t-test was used to analyze pre- and post-intervention differences. Quantitative findings showed significant improvements in mental health (M = 58.20 to 63.45; t(65) = 3.87, p 0.01) and social skills (M = 62.45 to 67.10; t(79) = 3.42, p 0.01) after implementing the peer-support program. Qualitative data reinforced these results, highlighting increased self-confidence, empathy, peer collaboration, emotional safety, and reduced bullying behaviors among students. The peer-support program effectively enhanced students' social-emotional development and promoted a more inclusive, supportive school environment. While the results are promising, limitations such as the absence of a control group and short-term measurement suggest the need for future longitudinal and controlled studies. These findings support the integration of peer-support models into inclusive school practices to improve psychosocial outcomes.